2021
DOI: 10.1021/acsaem.0c02060
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Site Activity Enhancement via Orbital Overlap in A2MnRuO7 (A = Dy3+, Ho3+, and Er3+) Pyrochlore Nanostructures

Abstract: Oxygen electrocatalysis at transition metal oxides is one of the key challenges underpinning electrochemical energy conversion systems, involving a delicate interplay of bulk electronic structure and surface coordination of the active sites. In this work, we investigate for the first time the structure-activity relationship of A2RuMnO7 (A = Dy 3+ , Ho 3+ , Er 3+ ) nanoparticles, demonstrating how orbital mixing of Ru, Mn, and O promotes high density of states (DOS) at the appropriate energy range for oxygen el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…Previous XES studies have shown that such spectra can be fitted as a linear combination of the Kβ of the constituent cation species. The normalized Mn-Kβ spectra for the reference samples (Figure S9) collected in this study were thus linearly combined to fit the Mn-Kβ spectra for LaMnO 3 and CaMnO 3 . Figure c,d shows the normalized Mn Kβ spectra for the LaMnO 3 and CaMnO 3 electrodes at the open-circuit potential (OCP, corresponding to 1.9 V) as a combination of the reference standards (fits for the different potentials can be found in Figure S10 and Table S5, as well as statistics of the fits in Table S6).…”
Section: Resultsmentioning
confidence: 99%
“…Previous XES studies have shown that such spectra can be fitted as a linear combination of the Kβ of the constituent cation species. The normalized Mn-Kβ spectra for the reference samples (Figure S9) collected in this study were thus linearly combined to fit the Mn-Kβ spectra for LaMnO 3 and CaMnO 3 . Figure c,d shows the normalized Mn Kβ spectra for the LaMnO 3 and CaMnO 3 electrodes at the open-circuit potential (OCP, corresponding to 1.9 V) as a combination of the reference standards (fits for the different potentials can be found in Figure S10 and Table S5, as well as statistics of the fits in Table S6).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a more fundamental approach to probing the electrocatalytic activity of transition metal oxides is to establish the link between the observed electrocatalytic activity and the element-projected density of states (p-DOS) of these strongly correlated materials across the energy (potential) range relevant to oxygen electrocatalysis. This approach has been used to rationalize the electrocatalytic activity of perovskites and pyrochlores, identifying Mn-based oxides as a key active element in ORR electrocatalysis. , …”
Section: Introductionmentioning
confidence: 99%
“…This approach has been used to rationalize the electrocatalytic activity of perovskites and pyrochlores, identifying Mn-based oxides as a key active element in ORR electrocatalysis. 24,25 LaMn x Ni 1−x O 3 (LMNO) provides an interesting test case to probe correlations between electronic structure and activity, given the contrasting electrocatalytic properties of Mn and Ni states toward ORR and OER. Bradley and co-workers performed a detailed high-throughput combinatorial analysis of the La−Mn−Ni composition space, concluding that Ni richcompositions provide optimum oxygen electrocatalysis, although without a clear correlation with the structure or electronic properties.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Celorrio et al linked the electrocatalytic activity to the presence of density of states (DOS) in the perovskite structure at potentials close to the ORR . Meanwhile, they reported the connection DOS in the region close to 1 V vs RHE. , Sun et al have shown that DOS can be promoted in the region close to 1 V by changing the oxidation state of Fe sites . However, unfortunately, the reduction peak is almost not observed in Figure S11, and the response between 1.1 and 1.2 cannot be determined to be the oxidation peak of Fe 2+ to Fe 3+ or/and the peak of pseudocapacitance within the potential investigated in the absence of oxygen.…”
Section: Results and Discussionmentioning
confidence: 99%